Barriers to the adoption of sustainable supply chain management practices: Moderating role of firm size - Sajjad Ahmad Baig; Muhammad Abrar; Aysha Batool; Muhammad Hashim; Rizwan Shabbir (Cogent Business & Management, 2020)
The reason behind the low adoption of sustainable supply chain management practices in developing countries is since emerging economies' supply chains face relatively more barriers to sustainability as compared to those which operate in developed countries. The research on the textile and apparel industry is mostly done in developed countries but empirical research on SSCM in developing countries is lacking. The purpose of this paper is to identify the key barriers that hinder the adoption of sustainable supply chain management practices and firm performance at the triple bottom line and what is the effect of firm size in tackling these barriers. Data is collected through a structured survey from B2B textile companies situated in Pakistan. After analyzing the exploratory factor analysis parameters, three groups of barriers are extracted: sectoral-economic, managerial, and supplier hindrance. The results exhibit that sectoral-economic and supplier hindrance has a significant effect on environmental management practices. Managerial barriers are significant with supply chain integration practices. Moreover, firm size significantly moderates the relationship of sectoral/economic barriers with environmental practices, and managerial barriers with social practices. Most importantly, the demand for societal awareness is required at both business and client levels to encourage organizations for adopting sustainable measures to gain competitiveness.
Keywords: 650; sustainability barriers; sustainable development; textile sector; sustainable supply chain management practices